Health and motivational education actions with women with breast cancer: Experience report of an initiative of medical students - de Lima Melo, Éllidy; de Queiroz Lima Neta , Rita; Lima de Souza, Gerdson; Paulo Oliveira Pinheiro , Cleoneide (Seven Editora, 2023)
Breast cancer is considered the second most frequent type of neoplasia in Brazil and is the main cause of neoplasia mortality among women, mainly because it is diagnosed in advanced stages. It is imperative to empower women to the risks of the disease and involve these women throughout the health-disease process.  DOI: https://doi.org/10.56238/tfisdwv1-089